Association of shiftwork and immune cells among police officers from the Buffalo Cardio-Metabolic Occupational Police Stress study. (3rd July 2017) - Wirth, Michael D.; Andrew, Michael E.; Burchfiel, Cecil M.; Burch, James B.; Fekedulegn, Desta; Hartley, Tara A.; Charles, Luenda E.; Violanti, John M.
ABSTRACT: Shift workers suffer from a constellation of symptoms associated with disruption of circadian rhythms including sleep abnormalities, and abnormal hormone secretion (e.g. melatonin, cortisol). Recent, but limited, evidence suggests that shift workers have elevated levels of circulating white blood cells (WBCs) compared to their day working counterparts. Interestingly, recent reviews highlight the strong linkage between the immune system and circadian rhythms which includes, but is not limited to, circulating cell populations and functions. The elevated levels of these WBCs may be associated with the increased chronic disease risk observed among this group. The purpose of this analysis was to examine the cross-sectional association between long- and short-term (3, 5, 7, and 14 days) shiftwork (SW) and counts of WBCs among officers in the Buffalo Cardio-Metabolic Occupational Police Stress (BCOPS) cohort. Data collection for this analysis took place among 464 police officers working in Buffalo, New York, USA between 2004 and 2009. Precise SW histories were obtained using electronic payroll records. Officers were assigned a shift type based on the shift (i.e. day, evening, night) that they spent a majority (i.e. ≥50%) of their time from 1994 to the data collection date for long-term SW. The same process was applied to SW over 3, 5, 7, and 14 days prior to data collection. A fasted blood sample collected in the morning of a non-work day was used for characterization of WBCs (total), neutrophils, monocytes, lymphocytes, eosinophils, and basophils. Potential confounding factors included demographic characteristics (e.g. age, sex, race), occupational characteristics (e.g. rank), health behaviors (e.g. smoking, alcohol consumption, diet), anthropometrics, and other biomarkers (e.g. lipids, hemoglobin A1C, leptin). Generalized linear models were used to estimate least square means of the immune cells according to SW categorization for long- and short-term SW histories. Compared to the day shift group, those working long-term night shifts had greater absolute numbers of total WBCs, neutrophils, lymphocytes, and monocytes (all p < 0.05). Those working mainly on the night shift over 7-days had elevated counts of WBCs, lymphocytes, and monocytes ( p < 0.05) compared to those mainly working day shifts. Results based on 3-, 5-, and 14-day SW were similar to the 7-day results. This study corroborates other studies with similar findings. However, this analysis provided insights into the effect of both long- and short-term SW on the number of circulating WBCs. SW may lead to disruption of circadian-influenced components of the immune system, which in term, may result in various chronic diseases. These findings, plus previous findings, may provide evidence that SW may lead to immune system dysregulation. Future research is needed to understand whether increases in immune cells among shift workers may be associated with the increased disease risk among this group.